Characterization of wavy root 1, an agravitropism allele, reveals the functions of OsPIN2 in fine regulation of auxin transport and distribution and in ABA biosynthesis and response in rice (Oryza sativa L.) - Wenqiang Li; Minjuan Zhang; Lei Qiao; Yunbo Chen; Dapeng Zhang; Xiuqing Jing; Pengfei Gan; Yangbin Huang; Junru Gao; Wenting Liu; Chunhai Shi; Hongchang Cui; et al. (Crop Journal, 2022)
Root system architecture is influenced by gravity. How the root senses gravity and directs its orientation, so-called gravitropism, is not only a fundamental question in plant biology but also theoretically important for genetic improvement of crop root architecture. However, the mechanism has not been elucidated in most crops. We characterized a rice agravitropism allele, wavy root 1 (war1), a loss-of-function allele in OsPIN2, which encodes an auxin efflux transporter. With loss of OsPIN2 function, war1 leads to altered root system architecture including wavy root, larger root distribution angle, and shallower root system due to the loss of gravitropic perception in root tips. In the war1 mutant, polar auxin transport was disrupted in the root tip, leading to abnormal auxin levels and disturbed auxin transport and distribution in columella cells. Amyloplast sedimentation, an important process in gravitropic sensing, was also decreased in root tip columella cells. The results indicated that OsPIN2 controls gravitropism by finely regulating auxin transport, distribution and levels, and amyloplast sedimentation in root tips. We identified a novel role of OsPIN2 in regulating ABA biosynthesis and response pathways. Loss of OsPIN2 function in the war1 resulted in increased sensitivity to ABA in seed germination, increased ABA level, changes in ABA-associated genes in roots, and decreased drought tolerance in the seedlings. These results suggest that the auxin transporter OsPIN2 not only modulates auxin transport to control root gravitropism, but also functions in ABA signaling to affect seed germination and root development, probably by mediating crosstalk between auxin and ABA pathways.